Research advances of correlations between bone and mineral metabolism disorders and immune dysfunction and infection in chronic kidney disease - Jin-jin Liu; Xiang Li; Ting Zhang; Zu-fei Yang; Ying Shen (Linchuang shenzangbing zazhi)
Chronic kidney disease （CKD） impairs immune function and renders patients susceptible to infection. The underlying mechanism of impaired immune function is multi-factorial. And mineral and bone disorder （MBD） is also involved. This review systematically summarized the mechanism of MBD biomarkers （vitamin D， fibroblast growth factor 23， parathyroid hormone， calcium & phosphorus） in regulating human immune function and the relationship between metabolic disorders and risk of infection. The potential values of vitamin D in regulating immunity and lowering the risk of infection provided rationales for clinically managing the risk of infection in CKD patients.